Paradoxical cause of weaning failure: Post tracheostomy foreign body causing non‐resolving pneumonia with worsening failure to wean. Issue 7 (27th May 2022) - Mangla, Loveleen; Thote, Sagar; Talwar, Dhruv; Talwar, Deepak
Abstract: The Percutaneous technique for tracheostomy has become the standard procedure, due to its ease in placement, minimal complications, and has almost replaced the traditional open (surgical) tracheostomy in intensive care units. We describe a case of broken tracheal cartilage which slipped into the tracheobronchial tree following percutaneous tracheostomy (PCT), impinging and causing collapse of medial basal segment of right lower lobe. Abstract : We describe a case of broken tracheal cartilage which slipped into the tracheobronchial tree following percutaneous tracheostomy (PCT), impinging and causing collapse of medial basal segment of right lower lobe. Our case highlights a rare complication of PDT leading to weaning failure, irony of situation being that it was done to treat the same.